When Tourism Meets Ecology: Community Narratives of Environmental Change in Indonesian Small Islands - Bastiar, Agus (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
This study investigates how tourism development shapes environmental change in Indonesia’s small islands, with a focus on community perspectives of sustainability and ecological vulnerability. Small islands are often promoted as idyllic destinations, yet they are ecologically fragile, with limited resources, sensitive ecosystems, and strong dependence on coastal environments. Using a qualitative research design, fieldwork was conducted in the Gili Islands (Lombok) and Karimunjawa (Central Java), where tourism has rapidly expanded over the past two decades. Semi-structured interviews were carried out with local fishers, homestay operators, tourism workers, and community leaders, complemented by participant observation of coastal activities and collection of local documents on environmental management. Thematic analysis revealed four central dynamics. First, participants described visible environmental degradation, including coral reef damage, waste accumulation, and declining fish stocks. Second, communities expressed concern over water scarcity and land-use conflicts driven by resort development. Third, tourism was perceived as both a threat and an opportunity, with livelihoods increasingly dependent on the very ecosystems under pressure. Finally, community members highlighted efforts to adapt, including local conservation initiatives, waste management programs, and calls for stricter regulation. The findings underscore that tourism-driven environmental change in small islands is experienced not only ecologically but also socially, as communities negotiate trade-offs between economic benefits and ecological sustainability.